AN APPROACH TO BPMN BASED BUSINESS PROCESS MODELS ANALYSIS AND OPTIMIZATION - Kopp, A. M.; Orlovskyi, D. L. (Radio Electronics, Computer Science, Control, 2018)
Context. Today, most organizations represent knowledge about their activities from a business processes point of view. At the same time, business process modeling is a subjective activity, which leads to errors associated with an analyst competence or i.e. with a poorly detailed subject area description. Thus, business process models should be analyzed for various kinds of shortcomings before they used for collecting, storing, and sharing of the organizational knowledge. Objective. The objective of the study is to develop an approach to the analysis and optimization of business process models used to represent the organizational knowledge. Method. A formal representation of business process models, based on directed graphs, has been considered in this study. Business process models design rules have been considered and formalized. A coefficient of business process models structural conformity to the design rules, which is based on the graphs redundancy characteristic and the business process models balancing coefficient, has been proposed. A formal approach to forming business process models enhancement recommendations has been proposed with considering the formalized design rules and the coefficient of structural conformity. Results. Calculations for models of products purchase and sale business processes, using developed software which is implemented the proposed approach to business process models analysis and optimization, have been performed. The design shortcomings of the considered models have been defined and the enhancement recommendations formed. Transformed models are error free and further can be used to represent organizational knowledge. Conclusions. The proposed approach allows to define the business process models design shortcomings and to develop recommendations for their elimination.